ABL-BCR expression does not correlate with deletions on the derivative chromosome 9 or survival in chronic myeloid leukemia - Fuente, Josu de la; Merx, Kirsten; Steer, E. Joanna; Müller, Martin; Szydlo, Richard M.; Maywald, Ole; Berger, Ute; Hehlmann, Rüdiger; Goldman, John M.; Cross, Nicholas C. P.; Melo, Junia V.; Hochhaus, Andreas (Blood, 2001)
Chronic myeloid leukemia (CML) is caused by a t(9;22)(q34;q11) reciprocal translocation that generates a BCR-ABLfusion gene on the 22q- or Philadelphia (Ph) chromosome and anABL-BCR gene on 9q+.12 Large deletions adjacent to the t(9;22) breakpoint on the derivative 9q+ chromosome have now been found, which result in genomic loss at both sides of the translocation breakpoint.3456 Recently, Huntly et al7 analyzed a large series of CML patients and confirmed that these deletions identify a subgroup of patients with relatively poor prognosis. However, the molecular basis of this survival disadvantage has not been identified. Due to its unique location spanning the chromosome 9/chromosome 22 junction, ABL-BCRappears as the most likely candidate for this role for the following reasons: (1) it occupies the minimal region of deletion in the reported cases6; (2) it is a “single-allele” gene whose deletion would result directly in total absence of the gene product, without a need to invoke a second event in a “2-hit” model8; and (3) it is known not to be expressed in approximately one third of CML patients,29 a frequency similar to that found for the 9q+ deletions.6